2021
DOI: 10.1152/jn.00630.2020
|View full text |Cite
|
Sign up to set email alerts
|

Expectations about motion direction affect perception and anticipatory smooth pursuit differently

Abstract: Smooth pursuit eye movements and visual motion perception rely on the integration of current sensory signals with past experience. Experience shapes our expectation of current visual events and can drive eye movement responses made in anticipation of a target, such as anticipatory pursuit. Previous research revealed consistent effects of expectation on anticipatory pursuit-eye movements follow the expected target direction or speed-and contrasting effects on motion perception, but most studies considered eithe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 70 publications
3
4
0
Order By: Relevance
“…In this case, the faster prior trial leads also to a significant increase in eye velocity in subsequent trials. Similar results were recently presented by Wu, Rothwell, Spering and Montagnini (2021) . In their work, they demonstrated that anticipatory pursuit follows the expected direction of a target, whereas perceptual results followed the opposite direction.…”
Section: Discussionsupporting
confidence: 92%
“…In this case, the faster prior trial leads also to a significant increase in eye velocity in subsequent trials. Similar results were recently presented by Wu, Rothwell, Spering and Montagnini (2021) . In their work, they demonstrated that anticipatory pursuit follows the expected direction of a target, whereas perceptual results followed the opposite direction.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the fact that participants were biased to report the direction of head rotation could also be explained by a higher-level response bias to answer in line with head rotation when stimulus uncertainty is high. This is supported by other findings of correlated heading and object motion biases ( Dyde and Harris 2008 , Wu et al. 2021 , Xing and Saunders 2022 ).…”
Section: Discussionsupporting
confidence: 89%
“…In other related work, Wu et al. (2021) used context trials of random-dot kinematograms (RDK) travelling in a certain direction within a trial block to build an expectation of direction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a recent study elegantly demonstrated this difference for single behavioral trials, 18 similar claims have been also made for serial dependence. 19,20 When repeatedly seeing the same movement sequence, perceptual decisions tend to be based on adaptation and integration of information across a longer time period. In contrast, oculomotor behavior only uses very recent information as priming to update sequential oculomotor responses and to allow better tracking responses.…”
Section: Discussionmentioning
confidence: 99%